Long-lasting headache in Covid - Carvalho, Fabiane Caxias de Paula; Monteiro, Gabriel de Almeida; Menezes, Letícia Soares Teles de; Matos, Larissa Silva de Oliveira; Santos, Ana Flávia Resende; Martins, Lorena do Carmo De Souza; Júnior, Odeon Parente Aguiar; Almeida, Rodrigo Franklin Pinheiro (Headache Medicine, 2023)
Full abstract in PDF.